Using the Altman and Sherrod models to predict financial failure (An applied study) (Journal of Hama University, 2024)
The research aimed to use the Altman and Sherrod models as one of the models for predicting financial failure in evaluating the performance of companies, by applying it to the data of the American retail company Wal-Mart.It also aimed to clarify the most important theoretical foundations of financial failure, and introduce the Altman and Sherrod models for predicting financial failure, determine their reality, and how to apply them. Many conclusions were reached, including: The value of Z for 2019 was lower than other years, and although the value of Z was outside the failure zone, the margin of safety decreased; Which indicates that the company was affected by the Corona epidemic and its repercussions, which negatively affected all areas of life this year.It was recommended that investors, financial analysts and auditors should be urged to use the Altman and Sherrod models to know the financial position of industrial companies and make appropriate investment decisions.